MENINGKATKAN RASA TANGGUNG JAWAB ANAK MELALUI METODE BERCERITA DAN ROLE PLAYING DI TK MUSLIMAT NU 5 SHOLEH YUSUF KIDAL TUMPANG - Hidayah, Nurul; Sarah Emmanuel Haryono; Choirul Huda (Al-ATHFAL: Jurnal Pendidikan Anak, 2025)
This study A sense of responsibility in early childhood does not develop automatically but rather through the imitation of behaviors and habits of people in their surroundings. This study aims to enhance children's sense of responsibility through storytelling and role-playing methods. The subjects of the study were 15 kindergarten B students at TK Muslimat NU 5 Sholeh Yusuf, located in Kidal Village, Tumpang District. The research employed Classroom Action Research (CAR) using the Kemmis and Taggart model, conducted in two cycles, each consisting of two meetings and involving four stages: planning, action, observation, and reflection. Data were collected through observation, interviews, and documentation, then analyzed qualitatively. The observed indicators of responsibility included the ability to complete tasks, take care of personal and others' belongings, and tidy up tools after use. The results showed a significant improvement from 62.7% in the pre-cycle to 81.6% in the second meeting of the second cycle. Specifically, 80% of the children were able to complete tasks, 80% could take care of personal belongings, and 86.6% were able to tidy up tools after use. These findings indicate that the implemented methods had not only a statistically positive impact but also reflected real behavioral changes in the children's daily lives. Storytelling allowed children to internalize moral values in an imaginative way, while role-playing provided direct experiences in practicing responsibility. Both methods align with Vygotsky’s constructivist theory, which emphasizes the importance of social learning. Therefore, storytelling and role-playing are effective in developing a sense of responsibility in early childhood. Keywords:  Storytelling Method; Role Playing; Responsibility